The Portrayal Of Marriage Life And Gender Role in Dickinson’s Selected Poems - Anita Rahmah Dewi; Siti Aminatuz Zuhria (FKIP, Universitas Billfath Lamongan, 2024)
This research aims to analyze the depiction of married life and gender roles as reflected in selected Emily Dickinson’s poems entitled “I gave myself to Him”, “I'm wife I've finished that”, “She rose to his requirements dropped, “Title divine is mine!”, and “A wife at daybreak I shall be”. This research uses feminist theory which focuses on the liberal feminism that is formulated by Marry Wollstonecraft. While the approach of this research applies context oriented due to it analyze the context of marriage life and gender role that are implicitly told in those selected poems. The findings in this research points out that in marital life and gender roles as reflected in Emily Dickinson's selected poems describes problems in married life where the main principle of feminism is that women have been subordinate to men since the beginning of human encounters. These poems present sharp exploration of the complexities and challenges that can arise in a marriage.